Assessing Ethoshunt as a Gamification-Based Mobile App in Ethics Education: Pilot Mixed-Methods Study - Zakaria, Noor Syamilah; Saripan, M Iqbal; Subarimaniam, Neerushah; Ismail, Alyani (JMIR Publications, 2020)
BackgroundGamification has remarkable potential in the learning space. The process of creating a gamified system and its influence on human behavior reflect the interaction between educators and machines. ObjectiveThe purpose of this pilot study was to present Ethoshunt as a gamification-based mobile app that can be used in teaching and learning ethics. MethodsThis study involved a mixed-methods research design. The researchers surveyed 39 undergraduate students who were introduced to Ethoshunt in order to examine the relationships between mobile app usability and positive emotions, ethical competency, and user experience. Affinity diagramming was used as a tool to organize the opinions and experiences of participants using featured gamification elements. ResultsGame dynamics and game mechanics explained the functionality of Ethoshunt. In addition, the learning flow through Ethoshunt was discussed. Overall, the findings were positive, and mobile app usability had the strongest relationship with positive emotions (r=0.744, P<.001), followed by ethical competency (r=0.686, P<.001) and user experience (r=0.614, P<.001). ConclusionsPositive emotions could be perceived as an important dimension in the development and usability of Ethoshunt. The researchers suggest that the gamification-based mobile app advocated in this study may provide ideas for ethics educators who wish to develop a technology-mediated learning environment.